La importancia del actor social: Un análisis del capital social en el ejido Emiliano Zapata en Amecameca, Estado de México - Díaz Morales, Andrés (2025)
In recent years, the concept of social capital has been taken up again to analyze human and social relationships. Social capital is manifested in networks of trust, cooperation and informal norms. This resource, influenced by exogenous factors and the agency of the actors, is key to community well-being. Using the methodology of social network analysis and integrating elements of presence of trust and social norms, in addition to the relevance of social actors, the necessary data was obtained. The analysis reveals that the ejido Emiliano Zapata work group functions as a community cohesive by personal ties and values, rather than by formal rules. Between 2012 and 2022, although the number of members decreased, the density of social relationships and trust increased. Key actors play a fundamental role, connecting the group with the outside world and helping to stabilize the organization through self-management and community norms.